Antifungal Efficacy of a Permanent Silicon Soft Liner Containing Silver Nanoparticles - Sareh Habibzadeh; Solmauz Eskandarion; Seyed Mahmoud Amin Marashi; Ghazal Yunesi; Mohamadjavad Kharazifard (Tehran University of Medical Sciences, 2021)
Objectives: This study aimed to evaluate the in vitro antifungal efficacy of addition of silver nanoparticles (SNPs) to Mucopren® silicone soft liner material. Materials and Methods: Twenty disc samples (8 × 2 mm) of Mucopren® silicone soft liner containing 0wt% (control), 0.5wt%, 1wt%, 2wt%, and 3wt% SNPs were fabricated. Samples were powdered and added to 150 mL of Sabouraud dextrose agar culture medium and placed on separate culture dish plates. Each plate was inoculated with 106 colony forming units per milliliter (CFUs/mL) of Candida albicans (PTCC 5027) according to the CLSI protocol, and incubated at 37℃. The colony count was verified at 24 h, and the antifungal effect of the samples was evaluated according to the percentage of viable cells in the 2 subgroups with/without thermocycling. Data were analyzed using SPSS version 20 via ANOVA and t-test (P<0.05). Results: All experimental groups showed higher antifungal activity than the control group, and this effect was dose-dependent (P<0.05). The lowest colony count was recorded in the 3wt% group. Thermocycling had no significant effect on the antifungal efficacy, except in 0.5wt% concentration of SNPs (P=0.013). Conclusion: Addition of SNPs to Mucopren soft liner conferred antifungal effects. Further mechanical stability and toxicity studies are still required.